Association of Pelvic Organ Prolapse and Changes in Bone Imaging Biomarkers in Postmenopausal Women with Low Bone Mineral Density - María Pérez Arguedas; Ernesto Bas Esteve; Alenda Jiménez García; Francisco Nohales Alfonso; Ana Jimenez-Pastor; Luis Martí-Bonmatí (Clinical and Experimental Obstetrics & Gynecology)
Background: To test the hypothesis that pelvic organ prolapse (POP) and osteoporosis are both manifestations of a connective tissue disorder, we evaluated whether there is an association between presence of POP and bone imaging biomarkers in postmenopausal women with low bone mineral density (BMD). Methods: A blind analytical, observational, and prospective cross-sectional study recruited 89 postmenopausal women with low BMD. Women were divided into those with absent/minimal or with moderate-to-severe POP. An X-ray of the spine was performed followed by a computational image analysis to quantify textural features on each vertebral body. Statistical analysis with a stepwise binary logistic regression model was used. Results: After 10 steps, the final model showed significance (p < 0.05) in the Omnibus coefficients test. The model classification results were high with over 80% success rates for both groups and an accuracy of 83%. The verification table showed that 39 of the 46 non-prolapsed patients were classified correctly, while 7 women were classified as having prolapsed. Among the 43 patients that had prolapsed, 35 patients were correctly classified while 8 were wrongly classified. The logistic regression analysis confirmed that both groups (prolapsed and non-prolapsed patients) can be differentiated using bone biomarkers on plain films. Most of the significant changes were found on the dorsal vertebrae. Conclusions: Pelvic organ prolapse is related to changes in bone imaging biomarkers, besides BMD. These results support the hypothesis that both pelvic prolapse and osteoporosis have a common causal origin.